Effect of liquiritin on human intestinal bacteria growth: metabolism and modulation. (26th February 2014) - Zhang, Wei; Jiang, Shu; Qian, Dawei; Shang, Er‐xin; Duan, Jin‐ao
ABSTRACT Licorice is one of the oldest and most frequently used prescribed traditional Chimese medicines. However, the route and metabolites of liquiritin by human intestinal microflora are not well understood and its metabolites may accumulate to exert physiological effects. Therefore, our objective was to screen the ability of the bacteria to metabolize liquiritin and assess the effect of this compound on the intestinal bacteria. Finally, six strains, comprising Bacteroides sp. 22 and sp.57, Veillonella sp. 31 and sp.48, Bacillus sp. 46 and Clostridium sp. 51, were isolated and their abilities to convert liquiritin studied. A total of five metabolites were identified using ultra performance liquid chromatography/quadrupole time‐of‐flight mass spectrometry in human incubated solution. The results indicated that hydrolysis, hydrogenation, methylation, deoxygenation and acetylation were the major routes of metabolism of liquiritin. On the other hand, effect of liquiritin on different strains of intestinal bacteria growth was detected using an Emax precision microplate reader. Growth of certain pathogenic bacteria, such as Enterobacter, Enterococcus, Clostridium and Bacteroides, was significantly repressed by liquiritin, while growth of commensal probiotics such as Lactobacillus and Bifidobacterium was less severely affected. Our observation provided further evidence for the importance of intestinal bacteria in the metabolism, and the potential activity of liquiritin in human health and disease. Copyright © 2014 John Wiley & Sons, Ltd.